Identifying Landmark Articles for Advancing the Practice of Geriatrics. Issue 11 (3rd November 2014) - Vaughan, Camille P.; Fowler, Rachel; Goodman, Richard A.; Graves, Taylor R.; Flacker, Jonathan M.; Johnson, Theodore M.
<x xml:space="preserve">Abstract</x> Landmark articles from the peer‐reviewed literature can be used to teach the fundamental principles of geriatric medicine. Three approaches were used in sequential combination to identify landmark articles as a resource for geriatricians and other healthcare practitioners. Candidate articles were identified first through a literature review and expert opinion survey of geriatric medicine faculty. Candidate articles in a winnowed list (n = 30) were then included in a bibliometric analysis that incorporated the journal impact factor and average monthly citation index. Finally, a consensus panel reviewed articles to assess each manuscript's clinical relevance. For each article, a final score was determined by averaging, with equal weight, the opinion survey, bibliometric analysis, and consensus panel review. This process ultimately resulted in the identification of 27 landmark articles. Overall, there was weak correlation between articles that the expert opinion survey and bibliometric analysis both rated highly. This process demonstrates a feasible method combining subjective and objective measures that can be used to identify landmark papers in geriatric medicine for the enhancement of geriatrics education and practice.